Exploiting the potential for services offshoring: Evidence from German firms - Peter S. Eppinger (Institut für Angewandte Wirtschaftsforschung (IAW), 2014)
Services offshoring is on the rise. Due to recent innovations in communication technologies, many services that used to be non-tradable can be delivered from distance today. Still, German services imports have grown much slower than exports over the past decades, indicating under-exploitation of the potential for services offshoring. To understand this development, the paper uses a newly combined dataset on German firms' services trade, balance sheets, and foreign affiliates during 2001-2012. Estimation of a firm-level gravity model confirms that more productive firms offshore more, reveals complementarities between services imports and exports, and points towards the importance of intra-firm services trade. The paper establishes that the level of services offshoring is lower in industries with greater offshoring potentials, as captured by their task compositions, but offshoring growth tends to be higher there. These findings indicate that there exists a sizeable potential for services offshoring due to remaining trade barriers, which is yet to be exploited.
Keywords: F10; F14; 330; offshoring; services trade; offshoring potential; trade in tasks